Issues of application of corpus methods in teaching foreign languages (Journal of Educational Sciences, 2016)
The article discusses the application of the Applied Linguistics methods in the teaching of foreign languages. The authors analyze the concept of “corpus” and the potential of the corpus approach to teaching a foreign language. A brief description of the corpus and the concordance-programis given. The analysis of such methods of corpus linguistics as automated extraction of information, teaching based on data, text searches in largescale corpuses (concordances) is presented. Moreover, the conditions that must be taken into account for the use of the corpus in the process ofteaching a foreign language are explained.
Keywords: corpus; concordance; foreign language teaching; corpus methods and tasks; communicative competence